1997
DOI: 10.1103/physrevb.56.8945
|View full text |Cite
|
Sign up to set email alerts
|

Classical critical behavior of spin models with long-range interactions

Abstract: We present the results of extensive Monte Carlo simulations of Ising models with algebraically decaying ferromagnetic interactions in the regime where classical critical behavior is expected for these systems. We corroborate the values for the exponents predicted by renormalization theory for systems in one, two, and three dimensions and accurately observe the predicted logarithmic corrections at the upper critical dimension. We give both theoretical and numerical evidence that above the upper critical dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
217
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(239 citation statements)
references
References 65 publications
18
217
0
1
Order By: Relevance
“…We have proven that the naive quantumclassical mapping fails for the sub-ohmic spin-boson model: Using a novel RG expansion around the delocalized fixed point, we have shown that the quantum transition at 0 < s < 1/2 is controlled by an interacting fixed point, whereas the corresponding classical longrange Ising model shows mean-field behavior. Thus, the spin-boson problem for s < 1/2 is equivalent neither to the classical Ising model nor to the corresponding (quantum or classical) O(1) φ 4 theory [10]. In physical terms the inequivalence can be traced back to the different disordered (delocalized) fixed points in the two situations (expansions around these fixed points are suitable to access the critical behavior for small s): In the quantum model the transverse field fully polarizes the spin in x direction (which can be viewed as a "condensate" of spin flips), whereas the high-temperature limit of the classical Ising model is simply incoherently disordered.…”
Section: Spin-boson Model: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have proven that the naive quantumclassical mapping fails for the sub-ohmic spin-boson model: Using a novel RG expansion around the delocalized fixed point, we have shown that the quantum transition at 0 < s < 1/2 is controlled by an interacting fixed point, whereas the corresponding classical longrange Ising model shows mean-field behavior. Thus, the spin-boson problem for s < 1/2 is equivalent neither to the classical Ising model nor to the corresponding (quantum or classical) O(1) φ 4 theory [10]. In physical terms the inequivalence can be traced back to the different disordered (delocalized) fixed points in the two situations (expansions around these fixed points are suitable to access the critical behavior for small s): In the quantum model the transverse field fully polarizes the spin in x direction (which can be viewed as a "condensate" of spin flips), whereas the high-temperature limit of the classical Ising model is simply incoherently disordered.…”
Section: Spin-boson Model: Numerical Resultsmentioning
confidence: 99%
“…As proven by Dyson [14] this model displays a phase transition for 0 < s ≤ 1. Both analytical arguments, based on the equivalence to a O(1) φ 4 theory [9], and extensive numerical simulations [10] show that the upper-critical dimension for the d-dimensional long-range Ising model is d + c = 2s, i.e., in d = 1 the transition obeys non-trivial critical behavior for 1/2 < s < 1. In contrast, mean-field behavior obtains for 0 < s < 1/2, with exponents [9,10] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional form (4.5) also coincides with the large-L behaviour of the free energy for N = 4 spin models with long-range interactions [31] (see also [26,47]). …”
Section: A Modified Finite Size Scaling Hypothesismentioning
confidence: 99%
“…In particular, recent analyses of systems at the upper critical dimension have adopted a finite-sized approach [21,29,31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%